KEMAMPUAN MENULIS KARANGAN PENGALAMAN PRIBADI SISWA KELAS VII SMP NEGERI 6 TERNATE - Kasim, Suhardi; Abdullah, Taib (Universitas Khairun, 2024)
Writing personal experience essays aims to improve students' skills in conveying ideas, ideas, and vocabulary development so that students' writing skills are more focused. Therefore, learning to write needs serious attention so that students are confident to express their ideas. Based on the root of the problem, researchers try to improve students' writing skills in personal experience essays. This research method uses the type of Classroom Action Research. The research subjects were 25 students of class VII SMP Negeri 6 Ternate. The data analysis technique used was descriptive qualitative. The results of this study showed that the ability to write personal experience essays in cycle one there were 17 students in the sufficient qualification, while cycle two experienced an increase of 24 students.